Influence of oncam feature in online conference on learning motivation during the pandemic - Muchammad Zidan Maulana; Azzahra Putri Dewanto (Curricula: Journal of Curriculum Development, 2022)
The impact of the COVID-19 pandemic has affected various aspects, including education. Since the pandemic, students have been forced to do online learning. Students’ unpreparedness for this change resulted in less effective teaching and learning activities. The students become inactive and find it difficult to focus during class. This, of course, affects using the oncam feature on the level of student learning motivation during the current pandemic. In this study, the researcher used a quantitative method by using a research instrument in the form of a form containing a series of questions related to how respondents’ learning behavior was while undergoing an online learning process using an online conference application that provides an oncam feature. Participants in this study were 42 active students at the Indonesian Education University, Department of Educational Curriculum and Technology batch 2020. Based on the data obtained, it was shown that the oncam feature could affect respondents' motivation level in learning. Therefore, according to these findings, the oncam feature in online learning can be paid more attention to maintain student learning motivation so that the learning process can run optimally   Abstrak Dampak pandemi COVID-19 telah mempengaruhi ke berbagai aspek tidak terkecuali pendidikan. Semenjak pandemi berlangsung, siswa dipaksa untuk melakukan pembelajaran secara daring. Ketidaksiapan siswa terhadap perubahan ini mengakibatkan kurang efektifnya kegiatan belajar mengajar. Para siswa menjadi tidak aktif dan sulit focus selama kelas berlangsung. Hal ini tentu saja mempengaruhi tingkatan motivasi belajar pada siswa. Penelitian ini bertujuan untuk mengetahui bagaimana pengaruh penggunaan oncam feature pada tingkatan motivasi belajar mahasiswa di masa pandemic saat ini. Pada penelitian kali ini peneliti menggunakan metode kuantitatif dengan menggunakan instrument penelitian berupa formulir yang berisi rangkaian pertanyaan yang berkaitan dengan bagaimana perilaku belajar responden saat sedang menjalani proses pembelajaran secara daring menggunakan aplikasi online conference yang menyediakan oncam feature. Peserta dalam penelitian ini adalah 42 mahasiswa aktif Universitas Pendidikan Indonesia Departemen Kurikulum dan Teknologi Pendidikan angkatan 2020. Berdasarkan data yang diperoleh, menunjukkan bahwa penggunaan oncam feature dapat mempengaruhi tingkatan motivasi responden dalam belajar. Oleh karena itu, menurut hasil temuan ini, penggunaan oncam feature pada pembelajaran daring bisa lebih diperhatikan lagi demi menjaga motivasi belajar mahasiswa agar proses pembelajaran dapat berjalan secara maksimal. Kata Kunci: Implementasi kurikulum; motivasi belajar; oncam feature; pandemi; pembelajaran daring